Escalas de desenvolvimento infantil e o uso com bebês - Rodrigues, Olga Maria Piazentin Rolim [UNESP] (FapUNIFESP (SciELO), 2012)
The present study aimed to describe the scales (tests or inventories) commonly used to evaluate the development of babies, in terms of objectives, population in which it is destined to, suggested material, what is evaluated and evaluation criteria. It also intended to analyze studies which employed instruments here described, from the late 90s, considering the objectives,the population evaluated, and the main results obtained and, finally, it aimed to identify health professionals who have employed it, since the articles published. The study highlights the important role of evaluating babies, as information source which help decision taking about the elaboration of essential or early intervention programs. However, it is difficult to find standardized instruments for Brazilian child population.

O presente estudo pretendeu descrever as escalas (testes ou inventários) comumente utilizadas para a avaliação do desenvolvimento de bebês, em termos de objetivos, população a quem se destina, material sugerido, o que avaliam e critérios de avaliação. Pretendeu, também, analisar estudos que utilizaram os instrumentos aqui arrolados, a partir do final da década de 90, considerando os objetivos, a população avaliada e os principais resultados obtidos e, finalmente, identificar profissionais da saúde que têm feito uso deles, a partir dos artigos publicados. O estudo aponta para o papel importante da avaliação de bebês como fonte de informação que subsidia tomadas de decisão acerca da elaboração de programas de intervenção precoce ou essencial. Todavia, observa-se a escassez de instrumentos padronizados para a população infantil brasileira.
Employment of scales to evaluate babies’ development
Keywords: Scales of infant development; Babies’ development; Essential stimulation; Early intervention; Escalas de desenvolvimento infantil; Desenvolvimento de bebês; Estimulação essencial; Intervenção precoce